EXPORT COMPETITIVENESS OF INDONESIAN CASSAVA COMMODITIES AND PROCESSED PRODUCTS IN THE GLOBAL MARKET - Frida Putri Purgito; Prasmita Dian Wijayati; Nuriah Yuliati (Jurnal Mahasiswa Agribisnis, 2026)
Cassava is a strategic commodity for Indonesia, yet it faces challenges from a 42% reduction in harvested area and the removal of fertilizer subsidies, increasing tapioca imports. This study analyzes the export competitiveness of Indonesian cassava across three downstreaming levels: primary (HS 071410), intermediate (HS 110814), and high value-added processed products (HS 190300). Using a descriptive quantitative method, this research integrates Revealed Comparative Advantage (RCA) and Export Product Dynamics (EPD) analyses using 2020–2024 time, series data from ITC Trade Map and FAOSTAT. Results show Indonesia has a strong comparative advantage in processed products (HS 190300) in Japan (RCA 11.53) and starch (HS 110814) in Sri Lanka (RCA 10.74). However, EPD analysis warns that raw products (HS 071410) are trapped in the Retreat quadrant, while processed products progressively act as a Rising Star. This study concludes that downstreaming is vital to maintaining national export competitiveness. The government must immediately intervene by providing fiscal incentives to the processing industry and ensuring upstream input availability for farmers. This strategy will overcome lost opportunities and strengthen Indonesia's position in the global market. Keywords: Cassava, EPD, Export Competitiveness, RCA